2012
DOI: 10.3846/20294913.2012.668373
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Bank Performance Using a Multicriteria Decision Making Model: A Case Study on Lithuanian Commercial Banks

Abstract: The paper presents an attempt to adopt a muticriteria decision making approach, particularly the Analytical Hierarchy Process (AHP) model, and to evaluate the performance of banks. The model is based on a system of various qualitative and quantitative criteria and their mutual relations. A system of indicators is created and described and each indicator is assigned a different degree of significance taking into account the needs and priorities of both internal and external evaluators. Model adaptation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…In particular, this is true for Lithuania in the field of finance. Lithuanian scientists pay some attention to the problem of evaluating domestic banks by MCDA methods (Brauers, Ginevicius, Podviezko, 2012;Zavadskas, Kaklauskas, Banaitis, Kvederyte, 2004;Ginevicius, Podvezko, 2008a;Ginevicius, Podvezko, Novotny, 2010;Ginevicius, Podvezko, Podviezko, 2012;Zvirblis, Buracas, 2010;Podviezko, Ginevicius, 2010;Stankeviciene, Mencaite, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this is true for Lithuania in the field of finance. Lithuanian scientists pay some attention to the problem of evaluating domestic banks by MCDA methods (Brauers, Ginevicius, Podviezko, 2012;Zavadskas, Kaklauskas, Banaitis, Kvederyte, 2004;Ginevicius, Podvezko, 2008a;Ginevicius, Podvezko, Novotny, 2010;Ginevicius, Podvezko, Podviezko, 2012;Zvirblis, Buracas, 2010;Podviezko, Ginevicius, 2010;Stankeviciene, Mencaite, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One of the best-performing indicators that evaluates (compares) the return on investment is Sharpe ratio [5]. The higher the Sharpe ratio is; the sooner the fund compensates for the risks involved [18]. The Sharpe ratio is calculated from the investment return rate minus the risk-free rate of return and dividing the result by the average standard deviation of the investment risk:…”
Section: Methodology For the Assessment Of Wheelset Wheel Weariness Amentioning
confidence: 99%
“…Indeed, in what concerns bank branch service quality in particular, there is a significant amount of research showing that despite the progress achieved, most of the limitations discussed above are still present (see also Ferreira et al 2011b;Stankevičiene and Mencait_ e 2012). Athanassopoulos (1997), for instance, highlighted the major limitations of Data Envelopment Analysis (DEA) as a nonparametric technique; Lee et al (2011) and Oliveira and von Hippel (2011) reported on several types of sample limitation; and Karatepe et al (2005) argued the need for more studies to address the issues discussed above.…”
Section: Related Workmentioning
confidence: 96%